2016
DOI: 10.1042/bcj20160290
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibrinogen glycation in ATTR: evidence for chaperone activity loss in disease

Abstract: Transthyretin amyloidosis (ATTR) belongs to a class of disorders caused by protein misfolding and aggregation. ATTR is a disabling disorder of autosomal dominant trait, where transthyretin (TTR) forms amyloid deposits in different organs, causing dysfunction of the peripheral nervous system. We previously discovered that amyloid fibrils from ATTR patients are glycated by methylglyoxal. Even though no consensus has been reached about the actual role of methylglyoxal-derived advanced glycation end-products in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Of the chaperones identified in this study, fibrinogen is the only chaperone that has previously been reported to directly interact with TTR (da Costa et al, 2011;Tang et al, 2009b). The chaperone activity of FGA is based on the isoform fibrinogen-420 (Tang et al, 2009a), and glycation of FGA results in a loss of function (Fonseca et al, 2016). Moreover, FGA can cause amyloid deposition as a consequence of genetic mutation (Yazaki et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…Of the chaperones identified in this study, fibrinogen is the only chaperone that has previously been reported to directly interact with TTR (da Costa et al, 2011;Tang et al, 2009b). The chaperone activity of FGA is based on the isoform fibrinogen-420 (Tang et al, 2009a), and glycation of FGA results in a loss of function (Fonseca et al, 2016). Moreover, FGA can cause amyloid deposition as a consequence of genetic mutation (Yazaki et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…Factors such as hyperfibrinogenemia, hyperinsulinemia, dyslipidemia, hypertension, obesity, decreased fibrinolysis, endothelial dysfunction, and changed platelet aggregability are known to influence thrombus formation in these individuals. 11,1416,1924 For example, fibrinogen concentration is an established independent risk factor for cardiovascular disease, regardless of vascular event history. 2529 Additionally, in animal studies, it is known that hyperfibrinogenemic mice exhibit changed fibrin fiber characteristics, quicker vessel occlusion, increased fibrin mass, and poor fibrinolytic behavior when compared to nonhyperfibrinogenemic controls.…”
Section: Introductionmentioning
confidence: 99%